Early identification of anxiety disorders: The role of the pediatrician in primary care. Issue 1 (2nd January 2018) - Carpenter, Aubrey L.; Pincus, Donna B.; Perrin, Ellen C.; Bair-Merritt, Megan H.; Mian, Nicholas D.
ABSTRACT: Anxiety disorders are the most common psychiatric disorder of childhood, and are associated with high risk for development of future psychopathology. Yet, pediatric anxiety disorders continue to be under diagnosed in primary care, leaving many children untreated. Pediatricians in primary care settings are in a unique position to detect child anxiety within the context of well-child visits. While important efforts are currently under way, such as increased behavioral screening, one of the most important challenges is that pediatricians do not receive an adequate level of training in the evaluation, management, and treatment of anxiety disorders. We review recent assessment initiatives in this area and call for increased efforts to promote early detection in primary care and reduce potential barriers for pediatricians, consistent with the movement toward integrated behavioral health models. Finally, we describe a current initiative that utilizes collaboration between psychologists and pediatric faculty to train pediatric residents to detect, diagnose, counsel, and refer young children with anxiety.